Control in the era of surveillance capitalism: An empirical investigation of Italian Industry 4.0 factories - Angelo Moro; Matteo Rinaldini; Jacopo Staccioli; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
We explore the extent to which the current technological trend, dubbed Industry 4.0, might increase forms of control inside organisations, by focussing on pivotal firms in the so-called Italian Motor Valley currently embracing its adoption. We find that Industry 4.0 technologies open up great possibilities for incorporating the three forms of control identified by Orlikowski (1991), i.e. personal, bureaucratic, and social, into technological artefacts, often blending them together. If, on the one hand, this implies a technical and theoretical feasibility of enforcing forms of "Big Brother" surveillance within the boundaries of organisations, and hereby of the workplace, on the other hand, the actual achievement of these possibilities depends on the organisational environment within which the new technologies are implemented.
Keywords: L23; L6; M54; O33; 330; Industry 4.0; Organisational Change; Control; Saturation of Working Time